1989
DOI: 10.1111/j.1365-2362.1989.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated serum bile acids as a marker of small intestinal bacterial overgrowth

Abstract: Non-invasive methods to detect small intestinal bacterial overgrowth often lack specificity in patients who have undergone an ileal resection or have an accelerated intestinal transit. Since elevated serum unconjugated bile acid levels have been found in patients with clinical signs of bacterial overgrowth, we studied the clinical value of unconjugated serum bile acids as a marker of small intestinal bacterial overgrowth. Patients with culture-proven bacterial overgrowth had significantly elevated fasting unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…When we compare our results to these previously determined thresholds, we see that the proportion of SUBA in our controls (22%) does approximate the expected value of 18% in healthy children, whereas children with history of IF and suspected SBBO had a much higher of fraction of SUBA at 87%. Absolute concentration of SUBA was higher as well in IF subjects compared with controls but only 5 of 14 IF subjects exceeded the proposed cutoff of 4 μM/L for SBBO described in adults by Masclee et al (1 of 11 controls did surpass 4 μM/L). Among these 5 IF subjects, however, 4 did have positive aspirates for SBBO.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…When we compare our results to these previously determined thresholds, we see that the proportion of SUBA in our controls (22%) does approximate the expected value of 18% in healthy children, whereas children with history of IF and suspected SBBO had a much higher of fraction of SUBA at 87%. Absolute concentration of SUBA was higher as well in IF subjects compared with controls but only 5 of 14 IF subjects exceeded the proposed cutoff of 4 μM/L for SBBO described in adults by Masclee et al (1 of 11 controls did surpass 4 μM/L). Among these 5 IF subjects, however, 4 did have positive aspirates for SBBO.…”
Section: Discussionmentioning
confidence: 49%
“…Elevated SUBA has been previously reported in adults with SBBO and is attributed to increased intestinal bacterial deconjugation of intraluminal bile acids in the presence of SBBO. Bolt 15 The majority (8 of 10) had SUBA concentrations >4 μM/L. In contrast, none of the controls without SBBO had SUBA concentrations above this value.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies in humans have documented unconjugated bile acids in intestinal fluid and serum, and increased concentrations are thought to be an indirect indicator of SIBO. [13][14][15][16][17][18][19] To date, only 1 study has measured serum total unconjugated bile acid (TUBA) concentrations in dogs. 20 That study suggested that such measurements could prove to be a more sensitive and specific test for SIBO than measurement of serum folate and cobalamin.…”
mentioning
confidence: 99%
“…Although unconjugated bile acid is cleared efficiently by the liver, levels tend to be higher than normal in patients with small bowel bacterial overgrowth [16]. This approach has not been accepted widely due to technical difficulty in measuring bile acid concentrations in blood [17] and due to potential confounding effects of liver disease and ileal bile acid malabsorption, which may lead to exposure of colonic bacteria to increased amounts of bile acid.…”
Section: Measurement Of Products Of Bacterial Metabolismmentioning
confidence: 98%